PROTEOLYTIC ACTIVITY OF MILK-CLOTTING ENZYMES OF DIFFERENT ORIGIN - D. S. Myagkonosov; D. V. Abramov; I. N. Delitskaya; E. G. Ovchinnikova (Пищевые системы)
The ratio of the milk-clotting activity (MCA) and proteolytic activity (PA) was compared for milk-clotting enzyme preparations (MEP) based on recombinant chymosin, chymosin of animal origin and microbial origin. The MCA value was measured in the international milk-clotting units (IMCU), the PA value was determined by the Anson method on the substrate from hemoglobin at 30 °C and рН 5.3. It was found that recombinant chymosins had the highest level of MCA/ PA: the group with MCA/ PA < ~1000 includes MEPs Chy-max® Extra 2235 Powder, Chy-max® Extra 600 Liquid and Renifer® 1800; the group with ~1000 < MCA/ PA < 1400 includes Chy-max® M 1000, Maxiren® 1800 and Chymax® Extra 2235 Powder; the group with MCA/ PA > 3500 includes MEP Chy-max® Supreme 1000. MEPs of animal origin had a lower indicator of MCA/ PA compared to recombinant chymosins, which for different trademarks of MEPs with different ratios of%chymosin to%pepsin was equal to: Naturen® Extra 220 (95/5) = 199.7 ± 8.0; rennet SF “Extra” (90/10) = 122.1 ±1.9; Kalase® 150 (80/20) = 115.1 ± 0.7; Naturen® Stamix (50/50) = 86.2 ± 0.2; rennet FS10 “Bovine pepsin” (10/90) = 38.7 ± 1.8. MEP of microbial origin had the lowest level of MCA/ PA among all three types of MEPs under study. MCA/ PA for different trademarks of MEPs of microbial origin was as follows: Meito® Microbial Rennet = 36.35 ± 0.48; Marzyme® 2200 MT = 31.03 ± 0.13; Fromase® 2200 TL = 18.57 ± 0.13; Fromase® 750 XLG = 16.06 ± 0.49.